Dupuytren's Disease Predicts Increased All-Cause and Cancer-Specific Mortality: Analysis of a Large Cohort from the U.K. Clinical Practice Research Datalink. Issue 3 (March 2020) - Kuo, Rachel Yi Ling; Ng, Michael; Prieto-Alhambra, Daniel; Furniss, Dominic
Abstract : Background: Dupuytren's disease is a common, chronic, fibroproliferative disease of the palmar fascia. The cause is unclear but includes genetic predisposition alongside environmental factors. Several studies have suggested an association between Dupuytren's disease and excess mortality. The authors aimed to evaluate this association in adult patients in the United Kingdom and identify the causes of mortality. Methods: The authors used a large primary care database (Clinical Practice Research Datalink) linked to the Office of National Statistics to identify patients with Dupuytren's disease between January 1, 1995, and December 31, 2013. Each patient was matched by age, sex, and general practitioner to five control patients without the disease. Cox regression models were used to study the association between Dupuytren's disease and all-cause and cause-specific mortality, adjusting for confounders. Results: A total of 41, 965 Dupuytren's disease patients and 209, 825 control patients were identified. The all-cause mortality rate was increased in both unadjusted (hazard ratio, 1.48; 99% CI, 1.29 to 1.70; p < 0.0001) and multivariable adjusted (hazard ratio, 1.43; 99% CI, 1.25 to 1.65; p < 0.0001) models in patients with Dupuytren's disease, 12 years after diagnosis. Excess mortality was secondary to a wide range of causes, including cancer (hazard ratio, 1.66; 99% CI, 1.27 to 2.17; p < 0.0001), an effect that persisted after adjustment for confounders. Conclusions: There is excess mortality associated with Dupuytren's disease that can be partially explained through environmental factors. From time of diagnosis in primary care, there is a 12-year window of opportunity for intervention to reduce the impact of these factors. The authors observed an increased risk of cancer mortality independent of confounders, and hypothesize a shared genetic risk between Dupuytren's disease and cancer. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II. Abstract : Supplemental Digital Content is available in the text.